NESTS SUCCESS AND EGGS DEVELOPMENT CONDITIONS ON IN-SITU INCUBATION OF MOLUCCAN SCRUBFOWL (Eulipoa wallacei) - Leimena, Handy Erwin Pier (Pattimura University, 2021)
The use of an external heat source for egg incubation will affect the nesting success of Moluccan scrubfowl (Eulipoa wallacei), thus ultimately determining their reproductive success. The purpose of this study was to calculate bird nest success and identify egg developmental condition from in-situ incubation. Field experiment method was used to estimate the effect of in-situ incubation treatment on bird nest success. A total of 220 egges were planted and 119 eggs were successfully incubated to produce chicks with an average nest success of 0.471 (47.07%). The average incubation time interval was 90 days (interval 86 – 94 days). Of the total eggs that did not hatch, 73.64% of the eggs did not show the embryonic formation during the incubation period. Ideal incubation conditions were important to trigger embrionic formation, so that in the end increase the probability of nest success and sustainable population recruitmen. This study also showed the potential of the Wai Learisa Kayeli estuary as an alternative nesting location for Moluccan scrubfowl on Haruku Island.